2021
DOI: 10.7441/joc.2021.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Model Based on Sustainable Development for Prioritizing Entrepreneurial Challenges Under a Competitive Environment

Abstract: In the post-recession period, the business environment in developing countries is still relatively undesirable. Based on the reports published, the number of closed entrepreneurs are significantly more than the number of those newly established. These statistics also reflect that the development of entrepreneurship faces several challenges. However, a strategic management program must be accurately conducted to effectively control entrepreneurial challenges based on the limitation of time and financial resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They found that innovativeness, networking, smart resource management, entrepreneurial culture and leadership, and entrepreneurial mindset all had an impact on SE. The most important factors were determined and entrepreneurial difficulties assessed using the Analytical Network Process (ANP) [27]. Using DANP (DEMATEL-ANP), many tourist entrepreneurship policy criteria have been prioritised in earlier studies [28].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…They found that innovativeness, networking, smart resource management, entrepreneurial culture and leadership, and entrepreneurial mindset all had an impact on SE. The most important factors were determined and entrepreneurial difficulties assessed using the Analytical Network Process (ANP) [27]. Using DANP (DEMATEL-ANP), many tourist entrepreneurship policy criteria have been prioritised in earlier studies [28].…”
Section: Review Of the Literaturementioning
confidence: 99%